Make Yourselves Gods: Mormons and the Unfinished Business of American Secularism. By Peter Coviello. Chicago: University of Chicago Press, 2019. 304 pp. 29.00 paper. - Park, Benjamin E. (Church history, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009640720001729/resource/name/firstPage-S0009640720001729a.jpg